Aaptamines from the Marine Sponge Aaptos sp. Display Anticancer Activities in Human Cancer Cell Lines and Modulate AP-1-, NF-κB-, and p53-Dependent Transcriptional Activity in Mouse JB6 Cl41 Cells. (22nd July 2014) - Dyshlovoy, Sergey A.; Fedorov, Sergey N.; Shubina, Larisa K.; Kuzmich, Alexandra S.; Bokemeyer, Carsten; Keller-von Amsberg, Gunhild; Honecker, Friedemann
Abstract : Aaptamine (8, 9-dimethoxy-1H-benzo[de][1, 6]naphthyridine) is a marine natural compound possessing antioxidative, antimicrobial, antifungal, and antiretroviral activity. Earlier, we have found that aaptamine and its derivatives demonstrate equal anticancer effects against the human germ cell cancer cell lines NT2 and NT2-R and cause some changes in the proteome of these cells. In order to explore further the mechanism of action of aaptamine and its derivatives, we studied the effects of aaptamine (1 ), demethyl(oxy)aaptamine (2 ), and isoaaptamine (3 ) on human cancer cell lines and on AP-1-, NF- κ B-, and p53-dependent transcriptional activity in murine JB6 Cl41 cells. We showed that compounds 1 –3 demonstrate anticancer activity in THP-1, HeLa, SNU-C4, SK-MEL-28, and MDA-MB-231 human cancer cell lines. Additionally, all compounds were found to prevent EGF-induced neoplastic transformation of murine JB6 Cl41 cells. Nuclear factors AP-1, NF- κ B, and p53 are involved in the cellular response to high and nontoxic concentrations of aaptamine alkaloids 1 –3 . Furthermore, inhibition of EGF-induced JB6 cell transformation, which is exerted by the compounds 1 –3 at low nontoxic concentrations of 0.7–2.1  μ M, cannot be explained by activation of AP-1 and NF- κ B.